1963
DOI: 10.5703/1288284313622
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Repeated Loading on Gravel and Crushed Stone Base Course Materials Used in the AASHO Road Test

Abstract: This paper presents the results of a laboratory investigation of the behavior of the AASHO Road Test gravel and crushed stone mixtures subjected to repeated loading. Cylindrical specimens were stressed trivially to levels approximating those which would be found in the base course of a highway pavement. The repetitive loadings were applied with equipment developed in the laboratories of the School of Civil Engineering at Purdue University.The materials used in the study were obtained from the site of the AASHO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
1
1

Year Published

1989
1989
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 0 publications
2
21
1
1
Order By: Relevance
“…It is noticed that the slope of the three curves changes abruptly at a degree of saturation around 75 % . This is lower than the 80-85 % value cited in the literature [2]. Figure 5 shows the effect of the deviator stress and degree of saturation on the permanent strain.…”
Section: Resultscontrasting
confidence: 45%
See 2 more Smart Citations
“…It is noticed that the slope of the three curves changes abruptly at a degree of saturation around 75 % . This is lower than the 80-85 % value cited in the literature [2]. Figure 5 shows the effect of the deviator stress and degree of saturation on the permanent strain.…”
Section: Resultscontrasting
confidence: 45%
“…Their analysis indicated an inverse correlation between k1 and kl 2 ) exists for the global class of all granular materials where (J is the bulk stress, and·k 1 and k 2 are regression constants. ' Also, they found that a relation exists between log k 1 and both the degree of saturation Sr and the logarithm of the unit volumetric compaction energy.…”
Section: Review Of Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Seed, Chan and Monismith (7) found that for compacted clays the frequency of load application was not related to total defor-AA.SHO mation. Haynes (8) TEST PROCEDURE…”
Section: E Lectronic Recording Equipmentmentioning
confidence: 99%
“…After mixing was completed, the soil was compacted in the 4 inch diameter by 8 When the probe had been inserted, the sample was transferred from the base of the split compaction mold to the base of a split aluminum saturation mold (Plate 4) . This mold was designed and fabricated for use during a previous research project by…”
Section: Sample Preparationmentioning
confidence: 99%